Hubungan Kejadian Asfiksia Neonatorum dengan Gangguan Fungsi Koklea pada Neonatus - Shinta, Nindya; Novira, Afita (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Hearing impairment on infants cause delayed development of speech, language, cognitive skills, and also social and emotional problems. The Joint Committee of Infants Hearing (JCIH) in 2007 stated perinatal asphyxia as one of the risk factors of infants hearing impairment. Hypoxia on asphyxiated neonates lead to the damage of outer hair cells (OHC) and edematous changes in stria vascularis in cochlea. The damage of OHC can be seen in the result of Otoacoustic Emission (OAE). The aim of this study was to analyze the correlation between neonatal asphyxia and cochlear dysfunction. This study was an observational analytic with cross sectional study design. Sampling was performed at dr. Soebandi and Kaliwates Jember Hospital November 29th 2019 – January 8th 2020 period in perinatology room. The sample is obtained by consecutive sampling. The data obtained were analyzed using Chi-square test with p-value < .,05. Out of 16 neonates, 8 neonates were with moderate asphyxia and other 8 neonates were not having any history of asphyxia. Cochlear dysfunction was noted in 3 (37.5%) neonates of moderate asphyxia and 6 (75%) neonates without history of asphyxia. The result of the study showed no significant correlation between moderate neonatal asphyxia and cochlear dysfunction (p=0.142).